Data for: The role of seed rain, seed bank and clonal growth in plant colonization of ancient and restored grasslands - Kapás, Rozália; Kimberley, Adam; Cousins, Sara (Stockholm University, 2024)
This dataset includes vascular plant species lists from grasslands with different land-use history in Södermanland, Sweden.The first dataset (Raw_experiment) contains (number of individuals occurring as seedlings (seedling) or clonal growth (vegetative) from the experiment that aimed to investigate the source of the species (such as arriving to the grassland via seed rain or regenerate from seed bank). It is collected in 32 plots (plot_type) from different treatment (seedtrap/control/ seedbank) in eight sites (site) and from different grassland type (type: restored/reference) over two years (month). The data is collected on 50 x 50 cm plot level. The second dataset (Raw_pool) contains the species presence in the surrounding of experiment (pool) with values describing their frequency (pool_freq=1-5) within the 40 inventoried plots (five 1 × 1 m plots per grassland). Empty values in the plant species lists read as NA´s. The detailed description of the experiment can be found in the Methods section of the paper (DOI..). Overview of each grassland site used in the experiment can be found in Table 1 of the related paper.
Keywords: Community ecology (excl. invasive species ecology); Terrestrial ecology; Ecology; Ekologi